2016
DOI: 10.1097/01.ogx.0000499755.80840.50
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Endometriosis During Abdominal or Laparoscopic Hysterectomy for Chronic Pelvic Pain

Abstract: (Abstracted from Obstet Gynecol 2016;127:1045–1053) Chronic pelvic pain is common in reproductive-aged women. A large number of women with chronic pelvic pain or endometriosis undergo hysterectomy: 10% to 32% for chronic pelvic pain and 5% to 19% for endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…The endometriosis rate in our study of 51% is consistent with rates reported in pain populations 21 . Higher-powered studies and reviews which question study definitions of CPP, report a lower rate (30%) of endometriosis amongst women with CPP 22 .…”
Section: Discussionsupporting
confidence: 91%
“…The endometriosis rate in our study of 51% is consistent with rates reported in pain populations 21 . Higher-powered studies and reviews which question study definitions of CPP, report a lower rate (30%) of endometriosis amongst women with CPP 22 .…”
Section: Discussionsupporting
confidence: 91%
“…The significance of musculoskeletal, or myofascial, pain in chronic pelvic pain conditions is becoming increasingly established . An estimated 25%‐40% of women undergoing diagnostic laparoscopic surgery for pelvic pain do not have an obvious structural diagnosis, suggesting their pain is not due to organ disease but may be due to myofascial dysfunction . Therefore, consideration of myofascial pain as a contributing cause of a patient's pelvic pain early in the workup may allow the patient to avoid unnecessary surgical procedures and, instead, pursue more appropriate conservative treatments.…”
Section: Introductionmentioning
confidence: 99%
“…55,56 Pelvic pain is a common symptom, and women with chronic pelvic pain do have a higher incidence of endometriosis, although histologic evidence of endometriosis is not always appreciable upon surgical examination. 57 Numerous etiologies of endometriosis have been proposed over time, including retrograde menstruation, metaplastic changes, and development from embryonic duct remnants. [58][59][60][61] Endometrial glandular epithelium typically resembles tight clusters of small cells with scant cytoplasm and cytologically bland nuclei with finely granular chromatin without prominent nucleoli ( Fig.…”
Section: Endometriosismentioning
confidence: 99%